2014
DOI: 10.1111/aogs.12476
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced CD200 and CD200R1 expression in human chorionic villi contributes to early spontaneous abortion

Abstract: There is an increase in inhibitory properties of human chorionic villi during normal pregnancy. The mechanism underlying ESA might be associated with enhanced expression of CD200 and CD200R in the trophoblast, leading to an upregulation of the immune response during the first trimester of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…12 Syncytiotrophoblast CD200 could have an autocrine self-stimulating effect as well as paracrine effects on CD200R + cytotrophoblasts. 12 Syncytiotrophoblast CD200 could have an autocrine self-stimulating effect as well as paracrine effects on CD200R + cytotrophoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Syncytiotrophoblast CD200 could have an autocrine self-stimulating effect as well as paracrine effects on CD200R + cytotrophoblasts. 12 Syncytiotrophoblast CD200 could have an autocrine self-stimulating effect as well as paracrine effects on CD200R + cytotrophoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…12 Based on CD200 −/− mouse data, CD200 exerts potent anti-inflammatory and anti-autoimmune effects which includes suppression of IL-17producing cells. However, a reduction in CD200R1 in villus syncytiotrophoblasts and villus cytotrophoblasts was more dramatic so CD200/CD200R1 ratios increased.…”
Section: Introductionmentioning
confidence: 99%
“…6 Human term placental trophoblast cells express CD200, and recently, Wang et al have reported CD200 expression on villous trophoblasts from healthy first trimester pregnancies, and a reduced expression on spontaneous abortion trophoblasts. 7,8 Wang et al also reported the presence of CD200R1 on first trimester villous trophoblasts from healthy pregnancies and reduced expression on miscarriage tissue. 8 The study by Wang et al is the first to suggest that CD200R1 might be expressed on nonlymphomyeloid cells in humans.…”
Section: Introductionmentioning
confidence: 94%
“…7,8 Wang et al also reported the presence of CD200R1 on first trimester villous trophoblasts from healthy pregnancies and reduced expression on miscarriage tissue. 8 The study by Wang et al is the first to suggest that CD200R1 might be expressed on nonlymphomyeloid cells in humans.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation